1991
DOI: 10.1007/bf00000807
|View full text |Cite
|
Sign up to set email alerts
|

The selectivity of a sequential extraction procedure for the determination of iron oxyhydroxides andiron sulfides in lake sediments

Abstract: Abstract. A popular sequential extraction procedure (Tessier et al. 1979) designed to extract metals partitioned in various sediment phases, was evaluated for its selectivity. Amorphous FeOOH, FeS, and FeS, were added separately to natural lake sediments and sequentially extracted. The selectivity of the sequential procedure for the added solid phases was evaluated by determining the difference in the mass of Fe extracted from treated and control sediments. In the experiments where sulfide minerals were added,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 24 publications
1
21
0
2
Order By: Relevance
“…This increase is mostly explained by the dehydratation and conversion of iron oxyhydroxides to more crystalline forms, not soluble in acidified NH 2 OH (Chao, 1972;Shuman, 1982;Chao and Liyi Zhou, 1983;Tipping et al, 1985;Shannon and White, 1991). For Cu, it is observed that the large organic pool was mainly shifted into the residual fraction.…”
Section: Residual Fractionmentioning
confidence: 98%
See 1 more Smart Citation
“…This increase is mostly explained by the dehydratation and conversion of iron oxyhydroxides to more crystalline forms, not soluble in acidified NH 2 OH (Chao, 1972;Shuman, 1982;Chao and Liyi Zhou, 1983;Tipping et al, 1985;Shannon and White, 1991). For Cu, it is observed that the large organic pool was mainly shifted into the residual fraction.…”
Section: Residual Fractionmentioning
confidence: 98%
“…Nonselectivity of the reagents and trace element redistributions among phases during fractionation are the main problems reported (Rendell and Batley, 1980;Tipping et al, 1985;Belzile et al, 1989;Bermond and Sommer, 1989;Calvet et al, 1990;Shannon and White, 1991;Bermond, 1992;Bermond and Eustache, 1993;Förstner, 1993;Xiao-Quan and Bin, 1993). Despite all the restrictions, sequential fractionation procedures have proved to be useful in the field of environmental analytical chemistry (Tessier and Campbell, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in addition to their targeted components, Fractions f2 and f3a may also extract metals associated with organic material adsorbed on particle surfaces, or surface sites on paniculate organic matter and metal oxides. Acid volatile sulphide (AVS), and metals associated with it, is reported to be partially extracted into Fraction f3 (Rapin et al 1986;Shannon & White 1991) instead of f4, and possibly even in Fraction f2 (Wallmann et al 1993). In addition, there is some evidence that solubilised metals may re-adsorb onto other components during extraction (Kheboian & Bauer 1987;Rendell et al 1980) especially Cu (Schriner 1994).…”
Section: Methodsmentioning
confidence: 99%
“…This process was proved to be a source of analytical bias in samples even accidentally exposed to free oxygen (Hjorth, 2004). Shannon and White (1991) also observed limited selectivity of the method of Tessier et al (1979) for iron sulfides in aerobically handled samples. Owing to its amorphous structure, FeS can be removed from the solid sediments during extraction steps I to III.…”
Section: Ironmentioning
confidence: 99%
“…Owing to its amorphous structure, FeS can be removed from the solid sediments during extraction steps I to III. Pyrite is reported to be more resistant to oxidation and is most effectively dissolved by a mixture of HNO 3 and H 2 O 2 (step IV of the extraction) (Shannon and White, 1991).…”
Section: Ironmentioning
confidence: 99%